y=-2×2+1

Replace the variable x with -2 in the expression.

f(-2)=-2(-2)3

Simplify the result.

Multiply -2 by (-2)3 by adding the exponents.

Multiply -2 by (-2)3.

Raise -2 to the power of 1.

f(-2)=(-2)(-2)3

Use the power rule aman=am+n to combine exponents.

f(-2)=(-2)1+3

f(-2)=(-2)1+3

Add 1 and 3.

f(-2)=(-2)4

f(-2)=(-2)4

Raise -2 to the power of 4.

f(-2)=16

The final answer is 16.

16

16

Convert 16 to decimal.

y=16

y=16

Replace the variable x with -1 in the expression.

f(-1)=-2(-1)3

Simplify the result.

Raise -1 to the power of 3.

f(-1)=-2⋅-1

Multiply -2 by -1.

f(-1)=2

The final answer is 2.

2

2

Convert 2 to decimal.

y=2

y=2

Replace the variable x with 0 in the expression.

f(0)=-2(0)3

Simplify the result.

Raising 0 to any positive power yields 0.

f(0)=-2⋅0

Multiply -2 by 0.

f(0)=0

The final answer is 0.

0

0

Convert 0 to decimal.

y=0

y=0

Replace the variable x with 1 in the expression.

f(1)=-2(1)3

Simplify the result.

One to any power is one.

f(1)=-2⋅1

Multiply -2 by 1.

f(1)=-2

The final answer is -2.

-2

-2

Convert -2 to decimal.

y=-2

y=-2

Replace the variable x with 2 in the expression.

f(2)=-2(2)3

Simplify the result.

Raise 2 to the power of 3.

f(2)=-2⋅8

Multiply -2 by 8.

f(2)=-16

The final answer is -16.

-16

-16

Convert -16 to decimal.

y=-16

y=-16

The cubic function can be graphed using the function behavior and the points.

xy-216-12001-22-16

The cubic function can be graphed using the function behavior and the selected points.

Rises to the left and falls to the right

xy-216-12001-22-16

Graph y=-2x^(2+1)